The Role of Educational Technology in Enhancing Digital Learning - Musthafa Ahyar Muttaqin; Michael Arson (Innovative Journal of Educational Research and Insights, 2026)
This study examines the role of educational technology in enhancing digital learning outcomes in contemporary educational settings. The research adopts a quantitative approach with a correlational design to analyze the relationship between the use of educational technology and students’ learning performance. Data were collected through a structured questionnaire distributed to students engaged in digital learning environments. The findings reveal that educational technology has a positive and significant effect on digital learning outcomes, particularly in improving student engagement, understanding, and academic achievement. The results also indicate that interactive tools, multimedia resources, and adaptive learning systems contribute to more effective and meaningful learning experiences. Furthermore, student engagement and personalized learning are identified as key factors that mediate the relationship between technology use and learning outcomes. However, the study also highlights several challenges, including limited access to digital infrastructure, lack of technical support, and varying levels of digital literacy among students and teachers. These challenges may affect the optimal implementation of educational technology. Therefore, it is essential for educational institutions to provide adequate resources, training, and support systems to maximize the benefits of digital learning. This study contributes to the understanding of how educational technology can be effectively integrated to improve the quality of education in the digital era.